Bears and Dogs: Animals, Animal Metaphors, and the Telling of Rape and Gendered Collectivity in Fredrik Backman's Beartown - Nygren, Anna (Children's literature (Storrs, Conn.), 2024)
Fredrik Backman's Beartown trilogy (2016–2021) tells the story of the fictional Swedish peripheral city Beartown and how it is affected by the rape of a young girl. This article examines the novels' use of animals and animal metaphors. Through Deleuze and Guattari's theories of becoming-animal, it investigates how humanity is negotiated through the closeness to nature.